Minimally Invasive Trans-Portal Resection of Deep Intracranial Lesions - Raza, S. M.; Recinos, P. F.; Avendano, J.; Adams, H.; Jallo, G. I.; Quinones-Hinojosa, A. (min - Minimally Invasive Neurosurgery, 2011)
Background: The surgical management of deep intra-axial lesions still requires microsurgical approaches that utilize retraction of deep white matter to obtain adequate visualization. We report our experience with a new tubular retractor system, designed specifically for intracranial applications, linked with frameless neuronavigation for a cohort of intraventricular and deep intra-axial tumors.Methods: The ViewSite Brain Access System (Vycor, Inc) was used in a series of 9 adult and pediatric patients with a variety of pathologies. Histological diagnoses either resected or biopsied with the system included: colloid cyst, DNET, papillary pineal tumor, anaplastic astrocytoma, toxoplasmosis and lymphoma. The locations of the lesions approached include: lateral ventricle, basal ganglia, pulvinar/posterior thalamus and insular cortex. Post-operative imaging was assessed to determine extent of resection and extent of white matter damage along the surgical trajectory (based on T2/FLAIR and diffusion restriction/ADC signal).Results: Satisfactory resection or biopsy was obtained in all patients. Radiographic analysis demonstrated evidence of white matter damage along the surgical trajectory in one patient. None of the patients experienced neurological deficits as a result of white matter retraction/manipulation.Conclusion: Based on a retrospective review of our experience, we feel that this accesss system, when used in conjunction with frameless neuronavigational systems, provides adequate visualization for tumor resection while permitting the use of standard microsurgical techniques through minimally invasive craniotomies. Our initial data indicate that this system may minimize white matter injury, but further studies are necessary.
Keywords: intraventricular; basal ganglia/thalamus; tube retractor; minimally invasive; frameless stereotaxis